PROSPEK PENGATURAN TINDAKAN KEBIRI KIMIA DAN PEMASANGAN ALAT PENDETEKSI ELEKTRONIK DALAM HUKUM POSITIF DI INDONESIA - Rahmawati, Adellia; Yuningsih, Henny; Nugraha, Adrian (Solusi, 2024)
Sexulall crimes algalinst children in Indonesial alre very worrying. Perpetraltors of sexulall violence algalinst children alre ulsulallly aldullts who alre close to the victim, whether in the falmily environment or the people in the environment where the child lives. Balsed on this, the government crealted al criminall lalw policy throulgh the formullaltion provisions in Lalw no. 17 of 2016 concerning the Stipullaltion of Government Regullaltions in Lieul of Lalw no. 1 of 2016 concerning the Second Almendment to Lalw no. 23 of 2002 concerning Child Protection Becomes al lalw thalt regullaltes chemicall calstraltion alnd the installlaltion of electronic detection devices for perpetraltors of sexulall violence algalinst children. Chemicall calstraltion is calrried oult by introdulcing alnti-alndrogen chemicalls, either vial pills or injections, into al person's body to wealken the testosterone hormone. In simple terms, chemicalls thalt alre pult into the body will redulce or even eliminalte libido or sexulall desire. The chemicall calstraltion alction formullalted in Alrticle 81 Palralgralph (7) of Lalw no. 17 of 2016 is not in alccordalnce with hulmaln rights. The alct of chemicall calstraltion hals the effect of losing al person's right to continule their offspring alnd fullfill their balsic needs als gulalralnteed in "Alrticle 28B palralgralph (1) of the 1945 Constitultion". The salme thing is allso stalted in "Alrticle 10 palralgralph (1) of Lalw no. 39 of 1999 concerning Hulmaln Rights”. The alct of chemicall calstraltion is allso contralry to Alrticle 7 of Lalw of the Repulblic of Indonesial Nulmber 12 of 2005 concerning Raltificaltion of the Internaltionall Covenalnt on Civil alnd Politicall Rights, Alrticle 2 of Lalw of the Repulblic of Indonesial No. 12 of 1995 concerning Corrections. Indonesialn Medicall Code of Ethics 2012, Alrticle 39 Lalw of the Repulblic of Indonesial no. 29 of 2004 concerning Medicall Pralctice. In sulbstalnce, chemicall calstraltion will resullt in the loss of al person's right to continule their offspring alnd fullfill their balsic needs als gulalralnteed in the 1945 Constitultion. Thuls, the prospect of chemicall calstraltion is not sulitalble for implementaltion in Indonesial, this is becalulse chemicall calstraltion hals al very lalrge negaltive impalct on heallth, alnd is allso not alpproprialte from al hulmaln rights perspective.